2020
DOI: 10.1038/s41598-020-67110-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of controlled-release urea on rice yield, nitrogen use efficiency and soil fertility in a single rice cropping system

Abstract: Overuse of nitrogen (N) fertilizer has led to low N use efficiency (NUE) and high N loss in single rice cropping systems in southeast China. Application of controlled-release urea (CRU) is considered as an effective N fertilizer practice for improving crop yields and NUE. Here, field experiments were conducted during 2015–2017 to assess the effects of two CRUs (resin-coated urea (RCU) and polyurethane-coated urea (PCU)) on rice yields, NUE and soil fertility at two sites (Lincheng town (LC) and Xintang town (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
6
39
0
1
Order By: Relevance
“…Nitrogen addition increased the performance of yield attributes, consequently increased grain yield and aboveground biomass. An increase in grain yield with increased NFR was also reported by Zhang et al ( 2020 ), while Chen et al ( 2020 ), as well as Jahan et al ( 2020 ), also reported similar results for increase in grain yield as well as aboveground biomass under increased N supply.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nitrogen addition increased the performance of yield attributes, consequently increased grain yield and aboveground biomass. An increase in grain yield with increased NFR was also reported by Zhang et al ( 2020 ), while Chen et al ( 2020 ), as well as Jahan et al ( 2020 ), also reported similar results for increase in grain yield as well as aboveground biomass under increased N supply.…”
Section: Discussionsupporting
confidence: 76%
“…We observed that N fertilization positively influenced stem density and panicle density under all the PDs in both seasons. According to Chen et al ( 2020 ), high N input resulted in increased stem buds' growth, which increased stem density. Stem density and increased tillering contribute and determine panicle density.…”
Section: Discussionmentioning
confidence: 99%
“…JW combination favoured N1 level nitrogen and produced a higher yield than other CMS hybrids. The results are consistent with observations made by Chen et al (2020), who found that nitrogen fertilisation affected positively and yield increased from 5.9 to 9.0 t/ha. Similarly, the find- ings also showed a great increase in yield and yield traits for different nitrogen fertilisation treatments.…”
Section: Discussionsupporting
confidence: 93%
“…There are many factors affecting the nitrogen utilization rate of rice, among which the nitrogen application quantity is one of them. Chen et al [24], Pan et al [25], and Rea et al [26] found that the partial productivity of nitrogen fertilizer for grain crops was 40~70 kg•kg −1 , the agronomic efficiency of nitrogen fertilizer was 10~30 kg•kg −1 , and the absorption utilization rate of nitrogen fertilizer was within the range of 30~50%. The normal nitrogen application level in South China is 120 kg•ha −1~1 50 kg•ha −1 [27,28].…”
Section: Discussionmentioning
confidence: 99%